2010
DOI: 10.1182/blood-2009-08-239517
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hemoglobin in sickle cell anemia: genome-wide association studies suggest a regulatory region in the 5′ olfactory receptor gene cluster

Abstract: In a genome-wide association study of 848 blacks with sickle cell anemia, we identified single nucleotide polymorphisms (SNPs) associated with fetal hemoglobin concentration. The most significant SNPs in a discovery sample were tested in a replication set of 305 blacks with sickle cell anemia and in subjects with hemoglobin E or beta thalassemia trait from Thailand and Hong Kong. A novel region on chromosome 11 containing olfactory receptor genes OR51B5 and OR51B6 was identified by 6 SNPs (lowest P = 4.7E-08) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
140
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(155 citation statements)
references
References 51 publications
11
140
2
2
Order By: Relevance
“…We selected five single nucleotide polymorphisms (SNP) from the HBS1L-MYB intergenic region and the BCL11A locus known to be associated with Hb F levels ( Table 2): rs1427407: the most significant SNP associated with Hb F levels within BCL11A, as reported by Menzel et al 12 This SNP is in high linkage disequilibrium (LD) with rs766432 (r 2 =0.98) in our sample, and with rs4671393 (r 2 =0.88 / D'=1) in the CEU samples based on the 1000 Genomes Project pilot phase 1 (CEU.1kG), for which effects on Hb F levels are also well-documented; 13,14 rs10189857: within BCL11A, documented to have an independent effect on Hb F levels; 15 rs9399137: the most significant SNP for Hb F levels within the HBS1L-MYB intergenic region in different populations, 5,12 in complete LD with a 3-bp deletion located in close proximity to four erythropoiesis-related transcription factor binding sites; 15,16 rs4895441: a SNP within the HBS1L-MYB intergenic region, widely reported to be associated with Hb F levels 5,17 and in complete LD with rs9402686 (r 2 =1 / D'=1 from CEU.1kG data), also reported to be independently associated with Hb F levels; 15 rs6904897: within the HBS1L-MYB intergenic region, this SNP is in complete LD with rs28384513 (r 2 =1 / D'=1 from CEU.1kG data), reported to be independently associated with Hb F levels.…”
Section: Selection Of Single Nucleotide Polymorphismssupporting
confidence: 76%
“…We selected five single nucleotide polymorphisms (SNP) from the HBS1L-MYB intergenic region and the BCL11A locus known to be associated with Hb F levels ( Table 2): rs1427407: the most significant SNP associated with Hb F levels within BCL11A, as reported by Menzel et al 12 This SNP is in high linkage disequilibrium (LD) with rs766432 (r 2 =0.98) in our sample, and with rs4671393 (r 2 =0.88 / D'=1) in the CEU samples based on the 1000 Genomes Project pilot phase 1 (CEU.1kG), for which effects on Hb F levels are also well-documented; 13,14 rs10189857: within BCL11A, documented to have an independent effect on Hb F levels; 15 rs9399137: the most significant SNP for Hb F levels within the HBS1L-MYB intergenic region in different populations, 5,12 in complete LD with a 3-bp deletion located in close proximity to four erythropoiesis-related transcription factor binding sites; 15,16 rs4895441: a SNP within the HBS1L-MYB intergenic region, widely reported to be associated with Hb F levels 5,17 and in complete LD with rs9402686 (r 2 =1 / D'=1 from CEU.1kG data), also reported to be independently associated with Hb F levels; 15 rs6904897: within the HBS1L-MYB intergenic region, this SNP is in complete LD with rs28384513 (r 2 =1 / D'=1 from CEU.1kG data), reported to be independently associated with Hb F levels.…”
Section: Selection Of Single Nucleotide Polymorphismssupporting
confidence: 76%
“…9,10 Several polymorphisms within intron 2 of the BCL11A gene have been strongly associated with Hb F levels: rs766432, rs4671393, rs1427407 and rs11886868, all in high linkage disequilibrium (LD) with each other. [11][12][13][14][15] Other independent signals in the same area were also identified with rs10189857 and rs7599488, in high LD, as well as rs7606173 and rs6706648, 13 also in high LD with each other. 12,13 In the HBS1L-MYB intergenic region, different SNPs have been described as being associated with Hb F variations in different studies: rs9399137, as well as rs4895441, rs9402686 and rs28384513.…”
mentioning
confidence: 78%
“…5 Moreover, it has been reported that the frequency of the JAK2 46/1 haplotype is increased in the context of severe inflammation, for instance Crohn's disease. 11,12 Altogether, the literature (reviewed in Table 1) shows that the common 46/1 haplotype is associated with predisposition to several types of disorders of variable severity: rare myeloid malignancies with or without JAK2/MPL mutation, including MPN and perhaps also acute myelomonocytic leukemia and NK-AML; inflammatory diseases; and possibly, reduced defense against infection. The mechanisms that underlie the increased risk of acquisition of MPN and JAK2/MPL mutation in carriers of the 46/1 haplotype are not understood.…”
mentioning
confidence: 99%
“…Third, even if the populations in which these variants were successfully associated represent all the main ethnic groups, not all the populations have been tested and some particular linkage disequilibrium structures might render the model less accurate in untested populations. [7][8][9][10][14][15][16][17][18] However, considering only countries with efficient health systems and screening programs, this retrospective study is a robust tool against mortality-driven bias. In such a context, mortality rates before ten years old are negligible (0 in our cohort), while over 90% of study patients were diagnosed, followed-up and treated before this age.…”
Section: Discussionmentioning
confidence: 99%
“…The whole cohort was genotyped for six markers at five loci that were already robustly associated with both HBF levels and/or the amelioration of b-thalassemia phenotype. 6,[14][15][16][17][18] Using Cox proportional hazard analysis for the age of regular transfusion start, we built a Thalassemia Severity Score (TSS) from genetic markers, tested its predictive ability, and, finally, made it available online at: http://tss.unica.it…”
Section: Introductionmentioning
confidence: 99%